Eco-metabolomics approach for understanding the chemodiversity of cocktails found on poison frogs (2021)
The superfamily Dendrobatoidea sensu, is one of groups of amphibians that exhibit one of the greatest diversities of chemical compounds. This family is distributed exclusively in Central and South America and is recognized because the skin of many species secretes alkaloids with promising pharmacological properties. Also, their toxicity is often correlated with the presence of bright coloration. However, current knowledge about chemical defenses in the superfamily Dendrobatoidea has two sources of bias. First, there is a lack of knowledge about the chemical profiles of cryptic (brown-colored) species compared to those with conspicuous coloration. Second, there has been little interest in characterizing metabolites other than alkaloids that may be involved in chemical communication, such as volatile organic compounds (VOCs). Additionally, to achieve these important discoveries, more than 10,000 animals of different species have been sacrificed to elucidate the chemical structures of these more than 500 alkaloids, so there is a need to design in vivo methods that allow studying the chemical profiles of species, especially those that are endemic or at high risk of extinction. Considering this, in this work we have employed different extraction and mass spectrometric techniques in combination with an eco-metabolomic approach to contribute to fill this gap of knowledge and to understand the proximate causes of variation in the defensive cocktails found in this group of amphibians. Employing a targeted approach in normal-phase gradient by HPLC-ESI-QTOF and an untargeted approach in reversed-phase gradient by HPLC-ESI-QTOF to analyze metabolites present in the cryptic Colostethus imbricolus, we found that neither tetrodotoxin (TTX) (a hydrophilic alkaloid previously found in another related dendrobatid), nor other tetrodotoxin analogs were detected in C. imbricolus.